THE INTERPRETATION OF THE DREAM MOTIF IN FOLK SONGS - Jabbor Eshonqulov (International Journal of Literature and Language Studies, 2026)
Folk songs are considered one of the most ancient and richest genres of folklore. Therefore, the period of their creation is rooted in antiquity and mythological perceptions. Songs initially emerged as seasonal ritual folklore specimens and, over time, gradually developed into a fully formed genre with distinct characteristics of their own. Folk songs have undergone an evolutionary process ranging from mythological perception to poetic thinking. For this reason, in the content and essence of songs, in their motifs and structure, as well as in the symbols and metaphors associated with them, we can trace the marks of this long historical process. When studying the interpretation of leading themes and motifs in folk songs, it is necessary to examine not only their place within the song structure, but also their mythological roots as a whole. From this perspective, the passages related to dreams in folk songs and the dream motif have been very little studied. When discussing the dream motif in folk songs, it is appropriate to dwell on two aspects in particular. The first is the harmony between metaphors and symbols in folk songs and the symbols and metaphors found in dreams. The second aspect concerns the relationship between dream and myth, and its harmony with the relationship between song and myth. In our article, through the analysis of the dream motif in folk songs, we examine such issues in detail.